Cnemaspis rammalensis sp. nov., Sri Lanka’s largest day-gecko (Sauria: Gekkonidae: Cnemaspis) from Rammalakanda Man and Biosphere Reserve in southern Sri Lanka - Vidanapathirana, Dulan Ranga; Rajeev, M. D. Gehan; Wickramasinghe, Nethu; Fernando, Samantha Suranjan; Wickramasinghe, L. J. Mendis (Zootaxa, 2014)
A new species of rock dwelling gecko belonging to the genus Cnemaspis is described from Sri Lanka based on a suite of morphological features. The species is the largest of its genus described from Sri Lanka so far (snout-vent length 52–54 mm) and is the second largest of the Western Ghats-Sri Lanka Biodiversity Hotspot. It may be diagnosed in details of both scalation (ventrals186–207; mid-subcaudals large; absence of precloacal pores; 15 femoral pores on each side; 22–23 and 23–25 subdigital lamellae on finger IV and on toe IV, respectively; smooth scales on tail dorsum) and colouration (five prominent trilobate shaped cream markings pointing towards head and extending from neck to vent).The species is found in a unique habitat in the Rammalakanda Forest, where it is threatened by deforestation.